2016
DOI: 10.1074/jbc.m116.764605
|View full text |Cite
|
Sign up to set email alerts
|

Lipid-tuned Zinc Transport Activity of Human ZnT8 Protein Correlates with Risk for Type-2 Diabetes

Abstract: Edited by F. Peter GuengerichZinc is a critical element for insulin storage in the secretory granules of pancreatic beta cells. The islet-specific zinc transporter ZnT8 mediates granular sequestration of zinc ions. A genetic variant of human ZnT8 arising from a single nonsynonymous nucleotide change contributes to increased susceptibility to type-2 diabetes (T2D), but it remains unclear how the high risk variant (Arg-325), which is also a higher frequency (>50%) allele, is correlated with zinc transport activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
85
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(92 citation statements)
references
References 22 publications
6
85
0
1
Order By: Relevance
“…The results reported by Merriman et al support this notion 27 . However, a potential additional role of ZnT8 at the level of the cell membrane cannot be ruled out.…”
Section: Discussionmentioning
confidence: 70%
“…The results reported by Merriman et al support this notion 27 . However, a potential additional role of ZnT8 at the level of the cell membrane cannot be ruled out.…”
Section: Discussionmentioning
confidence: 70%
“…The folding of the tagged-ZnT8 in the detergent extract of stably transfected INS-1E cells was examined by fluorescence size exclusion HPLC (FSEC). ZnT8 with a C-terminal GFP fusion tag (termed ZnT8-GFP) revealed a major monodispersed GFP fluorescence peak as reported previously (34). Inserting a FLAG epitope at one of the nine sites on the ZnT8 extracellular surface yielded only one tagged construct that exhibited a monodispersed FSEC profile.…”
Section: Resultsmentioning
confidence: 81%
“…A recent report, in which the activity of ZnT8 reconstituted in liposomes was investigated, concluded that the transport activity is dependent on the lipid environment, and inferred that the lipid environment affects zinc loading during insulin granule biogenesis . This report also noted that the T2D‐risk R325 ZnT8 variant consistently showed a small increase in zinc transport activity compared to the T2D‐protective W325 variant, which was revealed only with specific lipid compositions of the liposomes.…”
Section: Discussionmentioning
confidence: 85%
“…Second, this is the first report detailing that the W325R mutation causes significant differences in ZnT8 CTD dimer formation and stability. How or even if these effects in the CTDs lead to the altered transport function of the full-length proteins reported elsewhere [9], and ultimately to the relatively large increased risk of developing T2D for carriers of the R325 variant, will require further investigation. That the T2D-risk ZnT8 R325 variant is the more active form of the transporter suggests that people with the R325 variant may have an increased zinc content in their insulin granules as indicated by the data on human islets [41].…”
mentioning
confidence: 99%